Analysis and control of slope instability - Wu, Yu Sheng (2015)
Soil slope, a soil body with slant slope is a structure in civil engineering construction. If the shear strength of the soil slopes can resist shear stress, the soil slope is stable. Otherwise, it is unstable. Hence, the study on the stability of soil slope is of great significance for civil engineering construction. Limit Equilibrium Method (LEM) is the most common method in engineering practice. Through analysis of static equilibrium on unstable soil body, people can judge the stability of slope with this method in accordance with Mohr-Coulomb strength criterion. Ordinary method of slices is the most typical LEM. However, limited by assumptions, it cannot reflect the real stress-strain relationship or include complex loading, While Finite Element Method (FEM) can solve the problem. Slope instability is often triggered and aggravated by external factors, which often make the shear stress of the soil body increase or the shear strength decrease. So, in practical construction, people often consider various factors influencing slope stability determine earth work slope based on examination and design proper slope size to make slope crest load up to standard. If necessary, some supports might be installed to prevent slope instability. In this report, two cases are analyzed and summarized using software like Slide 6.0 and Plaxis 2D. The analysis reveals worthy experiences and highlights the practical value of case study.